Knowledge and Willingness Toward Organ Donation Among DPT Students at Isra University (Hyderabad) (Journal of Asian Development Studies, 2024)
Organ donation (OD) is a complex issue involving social, legal, ethical, and medical aspects. The need for organ transplants has increased due to a rise in disorders linked to poor lifestyle choices; however, awareness and knowledge of organ donation remain extremely low, particularly among medical students. This study aimed to assess the level of knowledge and willingness toward organ donation among Doctor of Physiotherapy (DPT) students at Isra University in Hyderabad. A cross sectional study was conducted from July to September 2024, using a validated questionnaire and a sample of 100 DPT students selected through stratified random sampling. Data were analyzed using IBM SPSS version 23. Findings revealed that 79% of DPT students were aware of organ donation. Only 12% recognized eyes and 34% identified kidneys for donation. Awareness of Pakistan's organ donation laws was noted in just 54%. Misconceptions were prevalent, with 51% believing that only living individuals could donate. While 38% expressed willingness to donate after death, only 16% would consent to the donation of a deceased family member's organs. The study concluded that significant gaps in knowledge and willingness exist among DPT students, highlighting the need for comprehensive education and awareness campaigns tailored to cultural and religious beliefs.